Didactic Sequence with Combinatory Analysis according to the SCORM Standard Seqüência Didática com Análise Combinatória no Padrão SCORM - Claudia Lisete Oliveira Groenwald; Lisiane Neto Zoch; Agostinho Iaqchan Ryokiti Homa (Universidade Estadual Paulista, 2009)
This paper presents a proposal for e-learning with the content of Combinatory, developed according to the SCORM standard and available on the collaborative platform ILIAS. The objective was to investigate the process of learning the didactic sequence, with the content of Combinatory, validating the capabilities of SCORM in the production of a multi-path didactic sequence using the principles of constructivist teaching and the use of electronic technologies in teaching. This approach emphasizes the individualized learning facilitated by the use of multi-path. Also presented are results of an e-learning experience implemented with nine students enrolled in the Mathematics Teaching Program at the Lutheran University of Brazil. Keywords: Mathematics Education. SCORM. Combinatory. Technologies in Teaching Mathematics. Electronic Learning. Este trabalho apresenta uma proposta de e-learning, com o conteúdo de Análise Combinatória, desenvolvida no padrão SCORM e disponibilizada na plataforma colaborativa ILIAS. O objetivo foi investigar o processo de ensino e aprendizagem da seqüência didática, com o conteúdo de Análise Combinatória, validando as capacidades do SCORM na produção de uma seqüência didática multicaminhos, utilizando os princípios construtivistas de ensino e o uso de tecnologias de ensino eletrônico. Esta abordagem dá ênfase ao aprendizado individualizado propiciado pelo uso de multicaminhos. Apresenta, também, os resultados da implementação do e-learning com nove alunos do curso de Licenciatura em Matemática da Universidade Luterana do Brasil. Palavras-chave: Educação Matemática. SCORM. Análise Combinatória. Tecnologias na Educação Matemática. Ensino Eletrônico.